Implementation of the Dengue Fever Eradication Health Promotion Program at the Simalingkar Community Health Center, Medan Tuntungan District - Luthfiah Khumaira; Zuhrina Aidha (LPPM Universitas Mohammad Husni Thamrin, 2025)
Health development in Indonesia currently faces dual challenges due to changing epidemiological patterns. Dengue Hemorrhagic Fever (DHF) is an endemic disease that remains a public health challenge, including in Medan Tuntungan District, one of the areas with high DHF cases in Medan City. The Simalingkar Community Health Center faces various obstacles in its efforts to eradicate DHF. The health promotion program implemented includes 3M Plus counseling, Mosquito Nest Eradication (PSN) activities through mutual cooperation, and distribution of larvicide as the main strategy for DHF control. This study aims to analyze the implementation of the health promotion program and identify obstacles to its implementation. The approach used was a qualitative case study design. Data were obtained through interviews, observations, and documentation with 15 informants, consisting of the head of the health center, the P2DBD coordinator, health promotion officers, neighborhood heads, PKK mothers, and the community. The results show that program implementation has been ongoing but is not optimal. 3M Plus counseling is still incidental and not routine. PSN is carried out periodically but with minimal education. Distribution of larvicide is not equitable. Key challenges include unclear program standards, limited resources, and low community participation. The program also focuses more on emergency response than promotion and prevention. Communication between implementers is quite good, but direct engagement with the community still needs improvement. Program implementation needs to be strengthened in terms of planning, resources, citizen participation, and cross-sector support.